Identification of the muscarinic acetylcholine receptor subtype mediating cholinergic vasodilation in murine retinal arterioles - Gericke, Adrian; Sniatecki, Jan J.; Goloborodko, Evgeny; Steege, Andreas; Zavaritskaya, Olga; Vetter, Jan M.; Grus, Franz H.; Patzak, Andreas; Wess, Jürgen; Pfeiffer, Norbert (Investigative ophthalmology & visual science, 2011)
To identify the muscarinic acetylcholine receptor subtype that mediates cholinergic vasodilation in murine retinal arterioles. Muscarinic receptor gene expression was determined in murine retinal arterioles using real-time PCR. To assess the functional relevance of muscarinic receptors for mediating vascular responses, retinal vascular preparations from muscarinic receptor-deficient mice were studied in vitro. Changes in luminal arteriole diameter in response to muscarinic and nonmuscarinic vasoactive substances were measured by video microscopy. Only mRNA for the M3 receptor was detected in retinal arterioles. Thus, M3 receptor-deficient mice (M3R−/−) and respective wild-type controls were used for functional studies. Acetylcholine concentration-dependently dilated retinal arterioles from wild-type mice. In contrast, vasodilation to acetylcholine was almost completely abolished in retinal arterioles from M3R−/− mice, whereas responses to the nitric oxide (NO) donor nitroprusside were retained. Carbachol, an acetylcholinesterase-resistant analog of acetylcholine, also evoked dilation in retinal arterioles from wild-type, but not from M3R−/−, mice. Vasodilation responses from wild-type mice to acetylcholine were negligible after incubation with the non-subtype-selective muscarinic receptor blocker atropine or the NO synthase inhibitor Nω-nitro-l-arginine methyl ester, and were even reversed to contraction after endothelial damage with 3-[(3-cholamidopropyl)dimethylammonio]-1-propanesulfonate. These findings provide evidence that endothelial M3 receptors mediate cholinergic vasodilation in murine retinal arterioles via activation of NO synthase.
Gesehen am 08.11.2023
Angenommen am 13. August 2011